Teaching methods used by internal medicine residents on rounds: what works? - Kulkarni, Vivek T (Adv Med Educ Pract, 2019)
BACKGROUND: The specific teaching methods used by internal medicine residents on walk rounds are unknown. OBJECTIVES: 1) To characterize in real time the specific teaching methods used by internal medicine residents on rounds and 2) to identify attributes of successful resident teaching on rounds. MATERIALS AND METHODS: We conducted a prospective mixed-methods study on inpatient medical services at a single academic medical center from September 2016 to January 2017. Participants were internal medicine residents (postgraduate year [PGY]-1, PGY-2, and PGY-3) and attending physicians. Teachers were PGY-2 and PGY-3 residents, and learners were PGY-1 residents. Residents’ teaching on rounds was observed and characterized according to resident demographics, specific teaching methods, and length of time. Participants completed a survey with Likert scale and free-text questions. RESULTS AND CONCLUSION: Among 136 surveys across 28 separate teaching encounters, we noted that PGY-3 residents’ teaching was rated significantly better than PGY-2 residents’ teaching. Teaching lasting >1 minute was rated significantly better than teaching lasting <1 minute. Free-text responses emphasized the value of immediate clinical relevance, citing published evidence, conciseness, clarity, and pertinence to the patient. Our findings may help guide internal medicine residents aiming to teach better on rounds and inform further research into specific resident teaching methods.